2017
DOI: 10.18632/oncotarget.16673
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal lipid hydrolysis provides substrates for lipid mediator synthesis in murine macrophages

Abstract: Degradation of lysosomal lipids requires lysosomal acid lipase (LAL), the only intracellular lipase known to be active at acidic pH. We found LAL to be expressed in murine immune cells with highest mRNA expression in macrophages and neutrophils. Furthermore, we observed that loss of LAL in mice caused lipid accumulation in white blood cells in the peripheral circulation, which increased in response to an acute inflammatory stimulus. Lal-deficient (-/-) macrophages accumulate neutral lipids, mainly cholesteryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 35 publications
(47 reference statements)
4
41
0
Order By: Relevance
“…Traditionally, phospholipids are thought to serve as the major source of fatty acids which upon cleavage by phospholipases, are oxidized enzymatically (e.g., lipoxygenases and cyclooxygenase) or non-enzymatically (e.g., reactive oxygen species), resulting in the formation of potent bioactive lipid mediators (LM). Recent work demonstrated that TGs are a potential source of these fatty acids 44 , 45 . Lysosomal acid lipase (LICH_Human), located in lysosomes, break down TGs and cholesterol esters into their associated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, phospholipids are thought to serve as the major source of fatty acids which upon cleavage by phospholipases, are oxidized enzymatically (e.g., lipoxygenases and cyclooxygenase) or non-enzymatically (e.g., reactive oxygen species), resulting in the formation of potent bioactive lipid mediators (LM). Recent work demonstrated that TGs are a potential source of these fatty acids 44 , 45 . Lysosomal acid lipase (LICH_Human), located in lysosomes, break down TGs and cholesterol esters into their associated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“… 10 ) studies. Lysosomal acid lipase is highly expressed in lung macrophages 46 , where it generates lipid mediators 45 . Lipid mediators have many signaling functions regulating inflammation 47 .…”
Section: Resultsmentioning
confidence: 99%
“…After uptake and internalization by macrophage SRs, modified LDL is transported to the late endosome/ lysosomes where the cholesteryl esters (CEs) are further hydrolyzed to free cholesterol (FC) and free fatty acids by lysosomal acid lipase [LAL, also known as lipase A (LIPA)] (Du et al, 2004;Ouimet et al, 2011;Dubland and Francis, 2015;Schlager et al, 2017). To prevent the potential cell toxicity caused by an excessive FC accumulation, FC can be re-esterified by acetyl-CoA acetyltransferases (ACAT) at the endoplasmic reticulum (ER) to form CE, which is stored in cytoplasm in the form of lipid droplets (LD).…”
Section: B Cholesterol Esterification and Hydrolysismentioning
confidence: 99%
“…The contribution of the lysosomal pathway to inflammatory signaling and lipid handling has been the subject of numerous studies. Lipid catabolism, as it occurs in lysosomes, is mainly achieved by the action of LIPA, whose deficiency and overexpression have been shown to alter immune (efferocytosis, T cell and macrophage function) and metabolic (insulin signaling, VLDL metabolism, ATM lipid content, polyunsaturated fatty acid (PUFA) release and lipid mediator synthesis) homeostasis [52][53][54]. In ATMs, the lysosomal program has been associated with the MMe phenotype, as evidenced by the enrichment of lysosome-relates genes Lipa and Lamp2, among others, in both obese mice [5,32] and humans [36].…”
Section: Lysosome-mediated Lipid Handlingmentioning
confidence: 99%